Tropes of The Crusades In Indonesian Muslim Discourse - Mark Woodward (Asia-Pacific Journal on Religion and Society, 2021)
"Crusade" is the movement of Europeans from the Middle Ages to conquer the holy land of Jerusalem from the hands of Muslims who have ruled for centuries there. This is a classic model of religious warfare. Crusaders increasingly colour the conversation of Muslims in terms of war, peace and global politics. The description of the crusade on Muslim militants and the president of the United States has led to the proliferation of crusading rhetoric even in a country like Indonesia where nota is not involved at all in the Middle East war in the 13th century. This article examines the problem of using crusades and semantic relations with the word Zionism in present-day Indonesia.